2019
DOI: 10.1016/j.ebiom.2019.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics reveals reduction of endocytic machinery components in gliomas

Abstract: Background Gliomas are the most frequent and aggressive malignancies of the central nervous system. Decades of molecular analyses have demonstrated that gliomas accumulate genetic alterations that culminate in enhanced activity of receptor tyrosine kinases and downstream mediators. While the genetic alterations, like gene amplification or loss, have been well characterized, little information exists about changes in the proteome of gliomas of different grades. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 85 publications
1
36
0
Order By: Relevance
“…As discussed also in later sections, many endocytic adaptors have links to cancer due to the aberrant signaling that is caused by their misregulation. In line with this, a recent study using quantitative proteomics revealed that AP-2α, AP-2β and AP-2σ and also other endocytic factors exhibit decreased expression levels in gliomas [48]. In addition to effects via its endocytic function, AP-2 could also modulate tumor cell migration and invasion by its non-canonical role in microtubule acetylation as recruiter of α-Tubulin Acetyltransferase (αTAT1) which affects directional cell locomotion and chemotaxis [49].…”
Section: Additional Links Of Ap-2 To Human Diseasementioning
confidence: 82%
See 2 more Smart Citations
“…As discussed also in later sections, many endocytic adaptors have links to cancer due to the aberrant signaling that is caused by their misregulation. In line with this, a recent study using quantitative proteomics revealed that AP-2α, AP-2β and AP-2σ and also other endocytic factors exhibit decreased expression levels in gliomas [48]. In addition to effects via its endocytic function, AP-2 could also modulate tumor cell migration and invasion by its non-canonical role in microtubule acetylation as recruiter of α-Tubulin Acetyltransferase (αTAT1) which affects directional cell locomotion and chemotaxis [49].…”
Section: Additional Links Of Ap-2 To Human Diseasementioning
confidence: 82%
“…Increasing the surface level of the respective tumor marker would improve the efficiency of the therapeutic approach. [40]; AP2S1 del17 mouse: embryonic lethality; neuron-specific AP2M1 KO: neurodegeneration and premature death [38]; IHC-specific AP2M1 KO: hearing deficit [12] AP2M1 mutation: epileptic encephalopathy [3]; AP2S1 mutation: familial hypocalciuric hypercalcemia type 3 [43]; AP-2α, AP-2β, AP-2σ downregulated in gliomas [48]; AP2A1, AP2A2 association with AD [47] Constitutive KO: behavioral alterations, epileptic seizures, premature death [105] Link to psychotic bipolar disorder [125] and to ASDs [126]; downregulated in gliomas [ Constitutive KO: increased cholesterol levels [230,231], altered ROMK response [235]; ARH/Dab2 DKO: pronounced hypercholesterolemia [256] Mutated in Autosomal recessive hypercholestero-lemia (ARH) [1] Arrestin1 (SAG) pSer/pThr in GPCR-NT Rhodopsin [295] Constitutive KO: extended response to light [295] Mutated in Oguchi syndrome: night blindness and sometimes retinal degeneration [300] Arrestin4 (ARR3)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that keeping the receptor amounts at the PM at relatively low levels minimizes unnecessary stimulation of the receptor at the cell surface by subthreshold stimuli. It was proposed that the impairment of endocytic machinery found in glioma cells might lead to prolonged RTK-dependent signaling [ 82 ]. In case of LTβR, endocytosis via multiple routes could constitute a mechanism of protection against over-activation of LTβR-evoked pro-inflammatory responses, that can be detrimental if not controlled [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…An unbiased quantitative proteomics analysis of human glioma biopsies revealed that up- or downregulation could be observed in multiple pathways. For instance, both clathrin-dependent and -independent endocytosis would be affected by a large reduction in various mechanical components related to the initiation, formation, and rupture of endocytic vectors, such as clathrin, AP-2 adaptins, and endophilins ( 105 ).…”
Section: Immunotherapy and Its Challengesmentioning
confidence: 99%